Assessment of the effects of scaling and root planing on blood glucose levels in type II diabetes patients: A pilot study - Uzma Rieyazulhuq Shaikh; Ravi V Shirahatti (Wolters Kluwer Medknow Publications, 2010)
Aim: To study the effect of the scaling and root planing of some blood glucose levels in Type II Diabetes patients. Study Population and Methods: The clinical study was conducted in 15 Type II diabetic patients of Dr. D Y Patil Dental College and Hospital, Pimpri, Pune. All the participants underwent a baseline examination for periodontal status using the community periodontal index of treatment needs and also estimation of fasting and post-prandial blood sugar levels. The participants received the intervention of scaling and root planing, as also routine oral hygiene instructions, and were recalled after one month for a final periodontal examination and blood sugar level investigation. The significance of difference between the means of the baseline and the final examination was tested using the paired 't' test. Results and Conclusion: There was no significant change in the fasting and post-prandial blood glucose levels in patients treated with scaling and root planing.